Illness explanatory models of depression among young people in low-resource settings: A qualitative study in Ghana and Zimbabwe - Denford Gudyanga; Rebecca Jopling; Moses Kumwenda; Franklin Glozah; Rufaro Mushonga; Edith Dambayi; Christopher Ayuure; Suzanne Dodd; Dzifa Attah; Arnold Maramba; Maria Anyorikeya; Lucy Owusu; et al. (PLoS ONE, 2026)
Background Depression among young people is a global public health issue, particularly common in low-resource settings like Ghana and Zimbabwe. Affecting around 10% of young people, depression often emerges between ages 15 and 24 and remains largely untreated due to stigma, limited resources, and cultural beliefs. This study explored the explanatory models of depression among Ghanaian and Zimbabwean young people, from the perspectives of young people, caregivers, healthcare workers, teachers, and community leaders, including policymakers, traditional and faith-based healers, to inform culturally relevant interventions. Methods Qualitative interviews were conducted in Ghana and Zimbabwe. Using purposive sampling, 133 semi-structured interviews and six focus group discussions were conducted with 53 participants, including young people aged 15–24 with lived experience of depression, high school students, caregivers, community leaders, teachers, and healthcare workers. Data were thematically analysed using NVivo 14 software to identify key patterns and themes. Findings Young people’s understanding and help-seeking behaviours reflected both emic and etic influences. Emic aspects included culturally shaped explanatory models shared by families, teachers, peers, and communities, including local idioms of distress and spiritual beliefs. Socio-economic stressors like poverty, family conflict, and academic pressure, though universally experienced, were often interpreted through culturally embedded narratives like spiritual causation, thus reflecting emic framing in participants’ accounts and influencing help-seeking in both countries. Etic aspects were evident in symptom descriptions aligning with behavioural (social withdrawal), emotional (sadness), cognitive (suicidal thoughts), and physical (fatigue) categories. Initial support was often sought from spiritual leaders, peers, and school-based resources. Conclusion This study provides a culturally grounded understanding of how young people in Ghana and Zimbabwe conceptualise depression, shaped by both emic and etic influences. Participants described depression using local idioms and spiritual explanations, while also recognising biomedical symptoms and socio-economic stressors. These findings underscore the need for interventions that integrate traditional beliefs with evidence-based approaches. Implementing multi-stakeholder approaches that engage families, schools, and spiritual leaders may be critical in reducing stigma, improving care access, and enhancing depression outcomes for young people.